POLA-POLA LEMBAGA EKONOMI ISLAM - Fahmi, Muhammad; Fatoni Bin Mohd Balwi, Mohd Abd Wahab; Mubaraq, Zulfi; Ayunin, Fikri Qurrata (Universitas Muhammadiyah Prof DR HAMKA, 2024)
The study of the Pattern of Islamic Economic Institutions is very important to be studied more deeply. This is because the study never ceases to be debated. The purpose of this paper is to understand 3 things: First, the Pattern of Islamic Economics. Second, Islamic Economic Institutions internal and external factors that affect society. Third, the positive and negative implications. The method used is literature review, with a descriptive approach based on qualitative theory, while data collection is descriptive and analyzed using content analysis techniques. The results found 3 things: First, there are 3 forms of Islamic Economic Patterns: Sharia Economy, Wellbeing, Islamic Banking. Second, internally there are 3 factors that influence: The methods of Islamic economic practice, Improving the quality of human resources, Expanding the number of Islamic Bank offices. As for externally there are 3 factors: Investor decline, public awareness, Muslim intellectual movement. Third, there are 3 positive implications: Anticipation of monopoly, Zakat and Rikaz policy, Impact of careful planning. Meanwhile, there are 3 negative implications: Limitation of Investment, complicated Akad for ordinary people, Decrease in Islamic Bank Customers. The conclusion that this paper shows that Islamic economics in principle and practice has the principle of justice and benefit. Keywords: Patterns, Institutions, Islamic Economics.